2021
DOI: 10.1101/2021.03.07.21253080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccine distrust in Colombian university students: Frequency and associated variables

Abstract: The study aimed to know the frequency and variables associated with COVID-19 vaccine distrust in students of a Colombian university. A cross-sectional study was carried out which participated emerging adult students of a Colombian university. A total of 1,136 students between 18 and 29 years (M= 22.0, SD = 3.0); most of them were female (66.0%), non-health students (82.8%), low-income (79.0%), and residents of urban areas (84.9%). It was frequent low institutional trust (74.8%), low cognitive, social capital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
12
1
2
Order By: Relevance
“…The review is based on carefully selected studies that focus on the research questions in this study. It includes studies that aim in understanding the correlates of COVID-19 vaccine hesitancy and the reasons why individuals intend to refuse to a COVID-19 vaccine, 8 , 19 prevalence of the acceptance of COVID-19 vaccine and their determinants, 27 the frequency and variables associated with COVID-19 vaccine 20 and understand COVID-19 vaccine hesitancy in an ethnically diverse and deprived population. 29 Other studies sought to study vaccine attitudes and the variables that influence vaccine intent in the context of the COVID-19 pandemic, 37 as well as to assess the adoption of COVID-19 vaccination in China and provide recommendations for vaccination strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review is based on carefully selected studies that focus on the research questions in this study. It includes studies that aim in understanding the correlates of COVID-19 vaccine hesitancy and the reasons why individuals intend to refuse to a COVID-19 vaccine, 8 , 19 prevalence of the acceptance of COVID-19 vaccine and their determinants, 27 the frequency and variables associated with COVID-19 vaccine 20 and understand COVID-19 vaccine hesitancy in an ethnically diverse and deprived population. 29 Other studies sought to study vaccine attitudes and the variables that influence vaccine intent in the context of the COVID-19 pandemic, 37 as well as to assess the adoption of COVID-19 vaccination in China and provide recommendations for vaccination strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Those Design health message targeted at hesitant group. (Campo-Arias & Pedrozo-Pupo, 2021) 20 USA The study aimed to know the frequency and variables associated with COVID-19 vaccine distrust in students of a Colombian university 1,136 Qualitative and quantitative study Survey design Likert scale with four point on trust in COVID-19 vaccine: “strongly disagree,” “disagree,” “agree,” and “strongly agree,” which are scored from 0 to 3. Colombian university students have a significant level of distrust in the COVID-19 vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting the literature, the current study found that the participants' attitudes towards vaccination did not differ according to their socio-demographic characteristics such as age and gender. [12,15] Although the socio-demographic characteristics did not affect the attitude towards vaccination, the type of the department where the students studied was found to be effective. In their study which they evaluated the attitudes of university students towards vaccination, Campo-Arias and Pedrozo-Pupo 15 found that 78.9% of the participants did not trust vaccination and these students were studying in departments unrelated to health.…”
Section: Discussionmentioning
confidence: 96%
“…[13,14] There are studies in the literature that examined university students' views. [13][14][15] This study is the first study evaluating the attitudes of health program students towards vaccination in our province.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [ 1 , 2 , 3 , 4 , 5 ] have found a greater availability and adherence to COVID-19 vaccination campaigns among the young (under-30), identifying, among the influencing factors, concerns of getting infected and transmitting the disease to family members and a high confidence in medical science and the actions of politicians in their country [ 6 , 7 , 8 , 9 ]. From an analysis of a data report [ 10 ], it emerged that in Italy, young people between 20 and 29 years old (for whom the vaccination campaign began in June 2021) were the most available category for vaccination, reaching an adherence percentage of 74% (first dose) and 65% (second dose) in just three months, compared to a percentage of 73% vaccinated for those over 30 years old who, on the contrary, received the call six months prior to them.…”
Section: Introductionmentioning
confidence: 99%